Single-particle mass analysis of intact ribosomes by mass photometry and Orbitrap-based charge detection mass spectrometry - Szu-Hsueh Lai (Elsevier, 2021)
Summary: Standard methods for mass analysis measure ensembles of thousand to millions of molecules. This approach enables analysis of monodisperse recombinant proteins, whereas some heterogeneous protein assemblies pose a significant challenge, whereby co-occurring stoichiometries, sub-complexes, and modifications hamper analysis using native mass spectrometry. To tackle the challenges posed by mass heterogeneity, single-particle methods may come to the rescue. Recently, two such approaches have been introduced, namely, mass photometry (MP) and Orbitrap-based charge detection mass spectrometry (CDMS). Both methods assess masses of individual molecules, albeit adhering to distinct physical principles. To evaluate these methods side by side, we analyzed a set of ribosomal particles, representing polydisperse ribonucleoprotein assemblies in the MDa range. MP and CDMS provide accurate masses for intact ribosomes and enable quantitative analysis of concomitant distinct particles within each ribosome sample. Here, we discuss pros and cons of these single-molecule techniques, also in the context of other techniques used for mass analysis.